Housing Asset Management Innovation: Digitalization and Partnership Strategy in Optimizing Ex-Tanjung Housing in Kutai Kartanegara Regency - Fatima Prativi; Anggi Rahajeng; Anisa Nurpita; Bagaskara; Maman Setiawan; Aini (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2025)
The management of local government assets plays a vital role in ensuring effective governance and the provision of public services. However, many regions face challenges in asset utilization, leading to inefficiencies and financial losses. One example is the Ex-Tanjung housing complex in Kutai Kartanegara Regency, which was originally intended to provide affordable housing for low-income households but has suffered from irregularities, weak oversight, and misuse. This study aims to identify appropriate strategies for improving the management of these housing assets so they can function sustainably and in accordance with their original purpose. The research employed a mixed-methods approach, combining primary data from focus group discussions, stakeholder mapping, and benchmarking with secondary data from government reports and statistical documents. SWOT analysis and a power–interest grid were applied to evaluate existing conditions and identify key stakeholders and their roles. The findings reveal that the Ex-Tanjung housing complex has strategic potential but is hindered by weak legal frameworks, poor governance, incomplete tenant and asset data, and many uninhabitable units. At the same time, strong housing demand, regulatory support, and opportunities for private sector involvement present avenues for improvement. The study concludes that integrated interventions are required, including regulatory strengthening, tenant regularization, physical rehabilitation, and the establishment of a clear management unit. These measures are essential to revitalize the housing complex and maximize its social and economic benefits.